Integration of Digital Media in Islamic Religious Education Learning in the Digital Era - Sevia Umi Wardini (International Journal of Islamic Pedagogical Research, 2026)
The rapid development of digital technology has significantly influenced educational practices, including the teaching of Islamic Religious Education (IRE). In the digital era, Islamic education is required to adapt to technological changes while maintaining its core values and objectives. This study aims to examine the integration of digital media in Islamic Religious Education learning and its role in enhancing the quality of the learning process. This research employs a qualitative approach using a library research design. Data were collected through an extensive review of books, scholarly journals, and academic publications related to digital media, Islamic education, and contemporary learning theories. The collected data were analyzed using content analysis techniques to identify key themes and conceptual patterns. The findings indicate that the integration of digital media in IRE learning supports active, meaningful, and value-oriented learning when implemented systematically and in accordance with Islamic principles. Digital media contributes to increased student engagement, contextual understanding of Islamic teachings, and the strengthening of moral and spiritual values. Furthermore, the study reveals that the effective integration of digital media aligns with constructivist, humanistic, and Islamic educational theories. The implications of this study emphasize the importance of enhancing teachers’ digital competence, developing pedagogically sound learning designs, and ensuring ethical and value-based use of digital media to optimize Islamic Religious Education in the digital era.